2008
DOI: 10.1096/fj.08-114637
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of the P2X7 receptor, an ATP‐gated channel, controls its expression and association with lipid rafts

Abstract: The P2X7 receptor (P2X7R) is an ATP-gated cationic channel expressed by hematopoietic, epithelial, and neuronal cells. Prolonged ATP exposure leads to the formation of a nonselective pore, which can result in cell death. We show that P2X7R is associated with detergent-resistant membranes (DRMs) in both transfected human embryonic kidney (HEK) cells and primary macrophages independently from ATP binding. The DRM association requires the posttranslational modification of P2X7R by palmitic acid. Treatment of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 55 publications
9
113
0
2
Order By: Relevance
“…This inhibition was not complete, however, suggesting that P2X7R may be only partially located in lipid microdomains ( Fig. 3 and unpublished data), which corroborates with published findings [27,88]. P2X7R has been shown to be at least partially localized to the lipid raft fraction in T cells, and the authors suggested that lipid raft localization facilitated ADP-ribosylation of P2X7R [89].…”
Section: Lipid Pathways and The P2x7 Receptor In The Immune Systemsupporting
confidence: 89%
See 1 more Smart Citation
“…This inhibition was not complete, however, suggesting that P2X7R may be only partially located in lipid microdomains ( Fig. 3 and unpublished data), which corroborates with published findings [27,88]. P2X7R has been shown to be at least partially localized to the lipid raft fraction in T cells, and the authors suggested that lipid raft localization facilitated ADP-ribosylation of P2X7R [89].…”
Section: Lipid Pathways and The P2x7 Receptor In The Immune Systemsupporting
confidence: 89%
“…Structural analysis of the P2X7R-PIP 2 binding motif (R385-K395) [59] reveals that this motif is close to the first cysteine-palmitoylated group found in the C terminus of P2X7R. These modified residues are associated with P2X7R membrane localization [88]. The cysteinepalmitoylated group could potentially anchor P2X7R in lipid rafts, concurrently facilitating an interaction between P2X7R and PIP 2 .…”
Section: Future Perspectivesmentioning
confidence: 96%
“…This phenotype resembles that of HEK-293 cells with P2X7 activation [39]. In fact, the activation of P2X7 can lead to different phenotypes, such as membrane blebbing and cell death by apoptosis or lysis/necrosis, depending on the cell type [41]. Taken together, there is still a possibility that P2 receptors are involved in ETX-induced death in MDCK cells and other cell types.…”
Section: Discussionmentioning
confidence: 94%
“…MVs are shed by microglia upon ATP activation 27 and originate from lipid rafts, 28 where the ATP receptor P2X 7 is localized. 29 Shed MVs selectively accumulate various cellular components, including soluble and integral proteins, lipids and nucleic acids and their composition reflects the activation state of donor microglia. Notably, microglia-derived MVs in the cerebrospinal fluid (CSF) have been recently identified as a novel biomarker of brain inflammation in humans.…”
mentioning
confidence: 99%